Taxless fiscal states: Lessons from 19th-century America and 21st-century China - Yuen Yuen Ang (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
How do modern fiscal states arise? Perhaps the most dominant explanation, based on the European experience, is that democratic institutions that limited the extractive power of states-exemplified by the 1688 Glorious Revolution in England-paved the way for the rise of fiscal capacity and subsequent prosperity. Revisionist accounts, however, reveal that this dominant narrative is flawed. In fact, numerous factors converged to enable the rise of European fiscal states, and in England, debt and land were particularly salient factors. Building off this literature, I bring attention to the role of 'taxless public financing' (i.e. financing public infrastructure through means other than taxation) in the making of fiscal states in two seldom compared cases: 19th-century America and 21st-century China. Both countries relied heavily on taxless financing to launch an infrastructure boom that spurred rapid growth along with massive corruption and financial risks.
Keywords: E62; E63; H3; O23; 330; taxless public financing; fiscal capacity; land; 19th-century America; China